A novel technology for turn-on voltage reduction of high-performance lateral heterojunction diode with source-gate shorted anode. (January 2019) - Wang, Zeheng; Yang, Di; Cao, Jun; Wang, Fangzhou; Yao, Yuanzhe
Abstract: A novel lateral heterojunction diode with a low turn-on voltage is proposed in this paper. Verified by theoretical analysis and simulations, it is partially relaxed InGaN channel that maintains the 2DEG under the recessed gate leading to a huge turn-on voltage reduction (by ∼39% maximum) and a low influence on BV, suggesting that the device owns a good potential in power applications such as bridge rectifier and wireless power transmission. Highlights: A novel lateral heterojunction diode with low turn-on voltage is proposed. The partially relaxed InGaN channel maintains 2DEG under the recessed gate. The turn-on voltage is reduced by 39% compared with the conventional diode. The BV is not influenced dramatically.